Unveiling shadows: exploring the dark side of digital transformation in Abu Dhabi - Masood Badri; Mugheer Alkhaili; Hamad Aldhaheri; Guang Yang; Muna Albahar; Saad Yaageib; Asma Alrashdi (Digital Transformation and Society)
Purpose – This research aims to investigate the negative aspects of digital transformation (DT) impacting various segments of society in the Emirate of Abu Dhabi, one of the seven Emirates comprising the United Arab Emirates. Specifically, it focuses on perceptions of participants to well-being: social connections and activities, physical health, mental health, the impact on the younger generation, and security/cybercrime. Design/methodology/approach – Using data from the 3rd Abu Dhabi Quality of Life Survey, which is an annual large-scale survey, this study employs analysis of variance and regression analysis to explore the associations between the perceived negative impact of DT and various well-being indicators. Findings – The study reveals that the perceived negative impact of digital transformation on the younger generation is of the highest concern, followed by concerns about mental health and social relationships. Results also show significant variations among different demographic categories. Among the perceived negative impacts, mental health, social trust, and happiness emerge as the most affected well-being indicators. Originality/value – The originality and value of this study lie in its large social survey sample of over 80,000 participants. The findings suggest that the negative effects of DT are not uniformly experienced across different segments of the population. The study highlights the need for further research on the adverse effects of DT and recommends that policymakers develop targeted strategies to address the specific needs of different community segments, particularly vulnerable groups. Additionally, it emphasizes the importance of adaptive policies for younger age groups to prepare them for a digital future.